2013
DOI: 10.1094/pdis-12-12-1206-re
|View full text |Cite
|
Sign up to set email alerts
|

Spilocaea oleagina in Olive Groves of Southern Spain: Survival, Inoculum Production, and Dispersal

Abstract: Olive scab caused by the mitosporic fungus Spilocaea oleagina is the most important foliar disease of olive. Limited information is available on pathogen survival and disease epidemiology; however, this information is essential for development of new control strategies. Pathogen survival and inoculum production on infected olive leaves and conidial dispersal were evaluated during 4 years in an olive orchard of the susceptible ‘Picual’ in southern Spain. Infected leaves in the tree canopy were important for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…On pecan trees, F. effusum overwinters mainly on the surface of twigs and nuts as stromata, which sporulate profusely in early spring (Demaree, 1924 ). The most important inoculum sources of F. oleagineum are the infected leaves remaining in the olive canopy (Graniti, 1993 ; Viruega et al, 2013 ), because the fungus does not produce conidia on fallen, scabbed leaves (Viruega et al, 2013 ).…”
Section: Venturia Species As Fruit Tree Pathogensmentioning
confidence: 99%
“…On pecan trees, F. effusum overwinters mainly on the surface of twigs and nuts as stromata, which sporulate profusely in early spring (Demaree, 1924 ). The most important inoculum sources of F. oleagineum are the infected leaves remaining in the olive canopy (Graniti, 1993 ; Viruega et al, 2013 ), because the fungus does not produce conidia on fallen, scabbed leaves (Viruega et al, 2013 ).…”
Section: Venturia Species As Fruit Tree Pathogensmentioning
confidence: 99%
“…Olive plants were sprayed with a conidial suspension of the pathogen, obtained from naturally infected leaves with sporulating olive leaf spot lesions, and adjusted to 1 · 10 5 conidia/mL. The plants were maintained for 48 h in a dark growth chamber at 15 to 17°C and 100% RH to favor infection (Viruega et al, 2013). Subsequently, the plants were placed in a shade-house until the appearance of symptoms.…”
Section: Experimental Design and Plant Measurementsmentioning
confidence: 99%
“…The disease is also called peacock's eye, and the main symptom in olive trees is circular lesions, sometimes with a chlorotic halo on the upper side of the leaves. Lesions change from a typical black scab to a whitish scab when high temperatures occur (Graniti, 1993;Viruega et al, 2013). Defoliation of the affected trees conduces to a significantly weakening, reducing yield (Graniti, 1993) and affecting organoleptic characteristics of the olive oil (Nigro et al, 2018).…”
mentioning
confidence: 99%
“…Carisse et al (2009) found with apple scab that the number of scabbed leaves per shoot was slightly aggregated, but the spatial pattern of lesions on leaves was highly aggregated (Carisse et al, 2011). Although the spatial pattern of olive scab (caused by F. oleagineum) has not been determined, studies on spore dispersal gradients showed that the numbers of conidia trapped near the inoculum source (<10 m) were linearly and positively related with cumulative rainfall (Viruega et al, 2013), and the number of dispersed conidia decreased exponentially with increasing distance from the inoculum source. Similar results were obtained for V. nashicola (Umemoto, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental requirements for infection and the dispersion patterns have been studied in detail for other Venturia spp., such as Venturia inaequalis (Becker and Burr, 1994;Hartman et al, 1999;Holb et al, 2004;Rossi et al, 2003;Stensvand et al, 1997;MacHardy, 1996;James and Sutton, 1982;Boric, 1985), V. nashicola (Li et al, 2005(Li et al, , 2003Lian et al, 2007;Umemoto, 1990), V. pyrina (Rossi et al, 2009;Spotts and Cervantes, 1991;Spotts et al, 1994;Villalta et al, 2000;2000b), F. carpophilum (Lan and Scherm, 2003;Lawrence and Zehr, 1982), F. effusum (Gottwald and Bertrand, 1982;Gottwald, 1985;Latham, 1982), and F. oleagineum (De Marzo et al, 1993;Lops et al, 1993;Obanor et al, 2010Obanor et al, , 2008bViruega et al, 2013Viruega et al, , 2011. These studies have been used to elaborate epidemiological models for some of these pathogens including V. pyrina (Eikemo et al, 2011), V. nashicola , V. inaequalis (Rossi and Bugiani, 2007;Xu et al, 1995), F. oleagineum (Roubal et al, 2013), and F. effusum (Payne and Smith, 2012).…”
Section: Introductionmentioning
confidence: 99%